Bisakah Angklung menjadi Instrumen Psikoedukatif? Studi Eksploratif pada Pemain Angklung - Retno Hanggarani Ninin; Roswita Amelinda (Jurnal Psikologi Islam dan Budaya, 2019)
Angklung is a unique traditional Sundanese music instrument involving a number of people to play it to produce a musical appearance. This uniqueness may indicate that angklung is not only an instrument of art, but also a psychoeducation instrument. This study explores the experience of angklung players in playing angklung and proves the use of angklung as a psychoeducation instrument. This study used explorative qualitative approach on seven angklung players. The results identify types of angklung player experience: audio-emotional, interactional (fellow players or coaches), and personal (interest, awareness, failure). Prerequisites of the use of psychoeducation instruments including the conversion of the role of the trainer to the educator, identifying specific behaviors in playing angklung as a simulation of the reality of social interaction, and providing instructions on how to play angklung optimally based on their parts. Angklung has psychoeducation potential to develop psychosocial skills (hablumminannaas) and servitude to God (hablumminnallah).